Analisis Sifat Dan Karakteristik Campuran Hangat Aspal Emulsi Dengan Variasi Perendaman - Rahmatullah, Rahmatullah; Nurdin, Abdul Rahim; Yunianti, Nur Hadijah (Program Studi Teknik Sipil Universitas Bosowa, 2023)
The purpose of this study was to analyze the properties and characteristics of the warm mixture of emulsified asphalt and to analyze the effectiveness of the characteristics of the warm mixture of emulsified asphalt with variations of immersion. The independent variable in this study is the immersion variation. The test method refers to the General Specifications of Highways 2018. The type of mixture used is Asphalt Concrete - Wearing Coarse. The performance was measured by testing Density, Stability, Flow, Marshall Quontient, voids in mixture (VIM), voids filled with asphalt (VFB), and voids in aggregate (VMA). The asphalt content used was 6.5%, then repeated immersion was carried out with variations of 3 days, 7 days, and 14 days of immersion. The results showed that the use of a warm mixture of emulsified asphalt and the length of immersion time affected the decrease in the value of the asphalt mixture properties. This is because the longer the immersion the asphalt adhesion to the mixture will decrease and the chance of losing the durability or durability of the mixture is also getting bigger. And from the results of the Marshall test using a warm mixture of asphalt emulsion, the best value for the characteristics is 3 days of immersion. Because it has a higher stability value so it will be able to withstand a greater load